2017
DOI: 10.1016/j.rppnen.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Hematological evaluation in males with obstructive sleep apnea before and after positive airway pressure

Abstract: Obstructive sleep apnea syndrome (OSAS) is a systemic inflammatory disease associated with cardiovascular consequences. Red blood cell distribution width (RDW), mean platelet volume (MPV), and platelet distribution width (PDW) are recognized biomarkers of cardiovascular morbidity/mortality. Limited data is available on the association between these parameters and OSAS severity and the relationship with positive airway pressure therapy (PAP). In this prospective study of male OSAS patients we analyzed hematolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…Significant decrease in MPV, hemoglobin and hematocrit levels in both OSAS groups after PAP treatment in OSAS is consistent with similar studies [29,30]. In our study, there was no statistically significant difference between the baseline and post-treatment platelet and PDW values, in which patients with moderate and severe OSAS were evaluated together.…”
Section: Discussionsupporting
confidence: 92%
“…Significant decrease in MPV, hemoglobin and hematocrit levels in both OSAS groups after PAP treatment in OSAS is consistent with similar studies [29,30]. In our study, there was no statistically significant difference between the baseline and post-treatment platelet and PDW values, in which patients with moderate and severe OSAS were evaluated together.…”
Section: Discussionsupporting
confidence: 92%
“…Sokucu et al [14] did not find any significant difference in platelet count between OSA group and controls after 6 months of CPAP treatment. Feliciano et al [39] also reported a significant decrease in platelet count of 48 male OSA patients (18 mild, 5 moderate, 25 severe) after 6 months of CPAP therapy. Similar to Feliciano at al.…”
Section: Discussionmentioning
confidence: 89%
“…Sokucu et al [14] reported that 6 months of CPAP therapy significantly decreased MPV value but increased RDW. Feliciano et al [39] showed that RDW significantly decreased after PAP treatment. We also found a decrease in the mean RDW value of our patients after treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Feliciano et al found that hemoglobin levels were 15.3±1.1 before treatment and 14.9±1 (p<0.0001) after treatment in a hematological parameter study on OSAS patients (8). Hemoglobin levels were elevated in OSAS and significantly decreased with treatment (8). Erythropoietin levels increase in hypoxic conditions, and there is a tendency for polycythemia to occur (9, 10).…”
Section: Discussionmentioning
confidence: 99%